Effect of Moringa oleifera leaf powder on skin mucosal immune responses and growth performance of guppy, Poecilia reticulata (Peter, 1860). (20th August 2020) - Bisht, Mayank; Kumar, Avdhesh; Shah, Tarang Kumar
Abstract: The present study was carried out to evaluate the effects of moringa leaf powder through dietary supplementation in guppy fish ( Poecilia reticulata ) on skin immune responses and growth performance. A total number of 240 fish (average body weight of 0.13 ± 0.01 g) were equally divided into four feeding groups including 0% (T0 ), 5% (MT1 ), 10% (MT2 ) and 15% (MT3 ) concentration of moringa leaf powder. The results showed that levels of lysozyme activity and alternative complement activity (ACH50) significantly increased with increase the moringa leaf powder ( p  < .05) concentration. Regarding the myeloperoxidase activity results, 15% doses of moringa leaf powder showed the highest amount of myeloperoxidase activity as compared to control group ( p  < .05). Total immunoglobulin content was increased significantly 10% and 15% treatments as well. In the present investigation, dietary supplementation of Moringa oleifera leaf powder had no significant impact on weight gain, net weight gain, specific growth rate, FCR and survival rate. The present results concluded that a dietary dose of 15% moringa leaf powder per kg of feed can significantly improve skin mucus immunity through enhanced production of mucus in the guppy.